MELOIDOGYNE AVLODI NEMATODALARI BILAN SUN’IY ZARARLANGAN BODRINGGA BT 26 SHTAMMINING TA’SIRI - Egamberganova A.Sh. , Egamberganova A.Sh.; Saidova Sh.O. , Saidova Sh.O.; Yorqulov J. M. , Yorqulov J. M.; G.B. Matmurotova , G.B. Matmurotova; G.B. Aramova , G.B. Aramova (Actual problems and prospects of the study of the fauna, 2024)
In our studies, the biopreparation BioSleep was taken as a model of the local strain Bt 26. Biogents Bt 26-1:100 (1 x 107 CFU/ml), Bt 26 - 1:200 (5 x 106 CFU/ml) in titers were used 2 times during the vegetation period. In the case of Bt 26 (1:200), the yield increased by 48.9%.